Intermittent fasting causes metabolic stress and leucopenia in young mice - O. M. Sorochynska; M. M. Bayliak; Y. V. Vasylyk; O. V. Kuzniak; I. Z. Drohomyretska; A. Ya. Klonovskyi; J. M. Storey; K. B. Storey; V. I. Lushchak (The Ukrainian Biochemical Journal, 2019)
Overweight and obesity became the worldwide epidemic resulting from overeating especially when a so-called Western diet rich in carbohydrates and fats is used. It is widely accepted that limitation of food consumption could help to withstand such state of adult organism, but information about younger groups is contradictory. The present study was undertaken to characterize the effects of intermittent fasting, using an every other day (EOD) fasting/feeding protocol, on hematological parameters and biochemical blood plasma indices in young mice from one to two months old. It was shown that intermittently fasted mice were characterized by a reduced body weight, reduced total number of blood leucocytes, lower glucose and lactate levels and higher activity of alanine aminotransferase and aspartate aminotransferase in blood plasma as compared with the age-matched control mice. To gain the same mass EOD animals needed to eat more food than ad libitum fed animals. These differences may probably be explained by a need to expend certain resources to combat stress induced by intermittent fasting. Our data showed that EOD feeding at a young age may negatively influence young mammals.